Enhanced Intranasal Absorption of Naltrexone by Dodecyl Maltopyranoside: Implications for the Treatment of Opioid Overdose. (30th January 2019) - Krieter, Philip; Gyaw, Shwe; Chiang, C. Nora; Crystal, Roger; Skolnick, Phil
Abstract: Based on its high affinity for μ opiate receptors and reported half‐life after oral administration, the pharmacokinetic properties of intranasal naltrexone were examined to evaluate its potential to treat opioid overdose. This study was prompted by the marked rise in overdose deaths linked to synthetic opioids like fentanyl, which may require more potent, longer‐lived opiate antagonists than naloxone. Both the maximum plasma concentration (Cmax ) and the time (Tmax ) to reach Cmax for intranasal naltrexone (4 mg) were comparable to values reported for a Food and Drug Administration‐approved 4‐mg dose of intranasal naloxone. The addition of the absorption enhancer dodecyl maltoside (Intravail) increased Cmax by ∼3‐fold and reduced the Tmax from 0.5 to 0.17 hours. Despite these very rapid increases in plasma concentrations of naltrexone, its short half‐life following intranasal administration (∼2.2 hours) could limit its usefulness as a rescue medication, particularly against longer‐lived synthetic opioids. Nonetheless, the ability to rapidly attain high plasma concentrations of naltrexone may be useful in other indications, including an as‐needed dosing strategy to treat alcohol use disorder.